A new ΔR value for the southern North Sea and its application in coastal research. (20th January 2021) - Enters, Dirk; Haynert, Kristin; Wehrmann, Achim; Freund, Holger; Schlütz, Frank
Abstract: Accelerator mass spectrometry (AMS) radiocarbon ( 14 C) dating of Cerastoderma edule (Linnaeus 1767) and Mytilus edulis (Linnaeus 1758) shells sampled in AD 1889 near the island of Wangerooge gave a new local correction factor ΔR of −85 ± 17 14 C years for the Wadden Sea area. The value is considerably higher than the available scattered data from the North Sea, which were obtained from pre-bomb growth rings of living Arctica islandica (Linnaeus 1767). This can be explained by the incorporation of 14 C-depleted terrestrial carbon into the shell material which compensates the intensified exchange of CO2 between atmosphere and shallow coastal water, e.g. by tidal currents. Additionally, two examples of application of the new Δ R value in coastal research give deeper insights into the dynamics of bivalve shell preservation in the Wadden Sea and the need for further research to clarify the Holocene reintroduction of Mya arenaria (Linnaeus 1758) into European waters.